A Scoping Review of the Physical Health Needs of Family Caregivers of Older Women With Breast Cancer - Felix, Mark Stephan; Kitcharoen, Patreeya; Le, Thi Ngoc Phuc; Puspitasari, Dewi Cahyani; Guo, Haihu (Journal of Population and Social Studies [JPSS], 2022)
This scoping review conducted mapping of relevant literature on the physical health needs of family caregivers of older women with breast cancer, gaps analysis, and suggests directions for future academic research. The PRISMA-ScR checklist by Tricco et al. (2018) guided the scoping review. Ten international databases were searched for academic articles published in English between January 2002 and January 2022. The 12,795 discovered articles were reduced to two sources of evidence. Extracted data were mapped out using a charting table. The analysis revealed a dearth of research on the subject of physical health of family caregivers of older women with breast cancer, a lack of detailed description of the physical health needs of family caregivers of older women with breast cancer, a lack of cultural, geographic, and ethnic diversity, a lack of studies on the physical needs/strains experienced by family caregivers aside from physical activity needs, underutilized research methodologies, gender differences that influence physical health needs of family caregivers, development of research tools, and lack of intervention/educational programs on physical health for family caregivers. Future research directions were suggested, and limitations were presented.